Trabalho agrícola na colheita do dendê : a contribuição da ergonomia na avaliação das condições de trabalho em uma empresa de médio porte no nordeste do estado do Pará - Robert, Leila de Fátima Oliveira de Jesus (Universidade Federal de São Carlos, 2017)
The main aim of this research is to understand how the operators deal with the variability of agricultural work in palm oil harvesting, the inherent strategies to the conditions of production and how they organize in the face of the specificities of this work, in a medium sized company in the State of Pará. To this, an adaptation had to be made in the method of ergonomic analysis of the work. The analysis contemplated the set of activities that integrate the harvest: cleaning, pruning, transportation and collection of loose fruit. Both in the look of the system as a whole and in the analysis of one by one. It was found that the distribution of the tasks is done in a fragmented way, in which each operator that was assigned to that task performs only that task. However, changes in management models are insufficient to indicate that agricultural work is influenced by Taylor/Ford models. The agricultural work of palm harvest involves a relationship in which, in part, the operator manages his own activity. So, the research suggests a management model based on the organizational specificities analyzed. It was observed the presence of little integration in the execution of the activities, of little community, although there is a good relationship between the operators. This fact is due to the tasks being organized by teams, within the parcels, under the command of a person in charge, it was verified a distribution in pairs or individual operator by planting lines, which results in monotony, reinforced by the fact of the team to work with plant of specific height. It was found that the agricultural work of the palm harvest tends to have much variability, for example, those classified as normal and predictable, such as encountering venomous animals and/or leaf thorn. We highlight problems with the use and handling of tools, which contribute to increase the efforts at work - the "handle" and the weight - require significant strategies associated with their adaptation, such as: tying alloys and filling with sand in the inner part of the aluminum cable. All these factors point to the understanding that the research extended the understanding of the "palm harvest" work and that, from this knowledge, the proposed actions generate other scientific research with intervention in the field that can bring improvements in the working conditions of these operators.
Keywords: Colheita de dendê; Análise ergonômica do trabalho; Trabalho agrícola; Dendê crop; Ergonomic analysis of work; Agricultural work; ENGENHARIAS::ENGENHARIA DE PRODUCAO